Penerapan Metode Design Thinking Dalam Implementasi User Interface Berbasis Website Studi Kasus JRO Sandat Property - Pratama, I Putu Ananda Andra; Paramitha, A.A. Istri Ita; Satwika, I Putu (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
Jro Sandat Property is a business engaged in the property sector which was established in 2014. Jro Sandat Property has services in the property sector, namely services to sell, rent, and develop villas in Bali. Jro Sandat Property still uses social media such as Instagram and Facebook as its marketing media and also a website for villa development property services, especially in the service of renting out villas currently inadequate on its website. Based on these problems, it is necessary to design and implement a website user interface that is relevant and effective for users of Jro Sandat Property so that it can improve user experience. The purpose of this research is to find out the design of the website user interface using the design thinking method on the Jro Sandat Property website. The research method used in this research is design thinking, this method is known as a comprehensive thinking process that concentrates on creating solutions that begin with a process of empathy for certain user-centered needs. The 5 stages that are carried out are empathize, define, ideate, prototype and test. The user interface design of the Jro Sandat Property website was built in the form of a prototype using the Figma application. The result of this research is a high-fidelity prototype of Jro Sandat Property website design that is user-friendly. This is directly proportional to the results of testing the prototype that has been built, using the System Usability Scale (SUS) testing method which gets a score of 81.25 which is included in the acceptable category.